Two Hands, Two Decks and a Theory in Action: Expanding Thinking Vocabularies of Learners in the 21st Century - Fisher, R. Michael (Journal of the Canadian Association for Curriculum Studies, 2017)
A complex 21st century offers us complex problems. We need more complex ways to think in order to solve them—such as Ken Wilber’s integral thinking. In this article, utilizing historical education referents for reconceptualizing curriculum in order to create more emphasis on meta-cognitive thinking about thinking, I offer a playful arts-based inquiry and performance of a unique curriculum device (a deck of thinking cards) that allows educators and researchers to bring forward their diverse vocabulary of types of thinking. I assert that it is time we passed on this vocabulary to our youth, to access and utilize in their own human potential growth and transformation into integral thinkers.